A CRITICAL DISCOURSE ANALYSIS: THE REPRESENTATION OF DONALD TRUMP IN THE REUTERS AND THE NEW YORK TIMES TOWARDS THE ISSUE OF #BLACKLIVESMATTER - Oka Cahyaningsih; Budi Eko Pranoto (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2021)
This research discusses about the representation of social actor in news media. The social actor that becomes the focus of this research is the U.S. President Donald Trump. The news media chosen by the researcher are Reuters and New York Times (NYTimes). The issue that become the focus in this research is #blacklivesmatter. Which that issue become trending in social media, because that issue, there are many Americans who do demonstrations in some cities, which asked Mr. Trump to do something related with that national issue. In this research, the researcher uses social actor theory from Van Leeuwen (2008). This research applies descriptive qualitative method.